PELATIHAN KETERAMPILAN MAKRAME BAGI IBU-IBU RUMAH TANGGA DI KELURAHAN LINGKAR BARAT KOTA BENGKULU - Dwi Anggraini; Hasnawati Hasnawati; Dalifa Dalifa (DHARMA RAFLESIA, 2018)
This training is motivated by the situation of housewives who spend time with less useful activities. On the other hand, making bags and wallets by using makrame techniques is developing in the community. For that, it is necessary to provide training to housewives to increase knowledge and skills about makrame. The method used is training which is divided into two stages, namely the stage of giving material and practice guided by the PPM team and six tutors. Increased knowledge is obtained from the difference in scores of participants after pretest and post-test. The results of the pre-test showed that only eightparticipants (25.8%) who received a score of ? 60, at post-test increased to 22 participants (70.97%) who received a score of ? 60. The conclusion of this activity is the knowledge and skills of the trainees increased. Keywords: Makrame, Art, Skills, Housewives